Old Challenges or New Issues? Genetic Health Professionals' Experiences Obtaining Informed Consent in Diagnostic Genomic Sequencing. Issue 1 (16th October 2020) - Vears, Danya F.; Borry, Pascal; Savulescu, Julian; Koplin, Julian J.
Abstract: Background: While integrating genomic sequencing into clinical care carries clear medical benefits, it also raises difficult ethical questions. Compared to traditional sequencing technologies, genomic sequencing and analysis is more likely to identify unsolicited findings (UF) and variants that cannot be classified as benign or disease-causing (variants of uncertain significance; VUS). UF and VUS pose new challenges for genetic health professionals (GHPs) who are obtaining informed consent for genomic sequencing from patients. Methods: We conducted semi-structured interviews with 31 GHPs across Europe, Australia and Canada to identify some of these challenges. Results: Our results show that GHPs find it difficult to prepare patients to receive results because a vast amount of information is required to fully inform patients about VUS and UF. GHPs also struggle to engage patients – many of whom may be focused on ending their 'diagnostic odyssey' – in the informed consent process in a meaningful way. Thus, some questioned how 'informed' patients actually are when they agree to undergo clinical genomic sequencing. Conclusions: These findings suggest a tension remains between sufficient information provision at the risk of overwhelming the patient and imparting less information at the risk of uninformed decision-making. We suggest that a shift away from 'fully informed consent' toward an approach aimed at realizing, as far as possible, the underlying goals that informed consent is meant to promote.